Family support and adherence to treatment in people affected by tuberculosis - Cesar Raul Castro Galarza; Maritsa Julia Camarena Cristóbal; Ilse Faustina Fernandez Honorio (Medisur)
Background: Adherence to treatment in tuberculosis is relevant, both for its effect to be successful and to limit the emergence of drug resistance. Objective: to determine the relationship between family support and adherence to treatment in patients with tuberculosis. Methods: descriptive and correlational study, with a sample made up of 38 patients diagnosed with tuberculosis, who received treatment at the Manuel Ángel Higa Arakaki Hospital, to whom a questionnaire was applied to assess the degree of family support and level of adherence to treatment, which was adapted for people affected by tuberculosis. The data collected were processed using Kendall's Tau b test. Results: 44.74 % of the patients showed moderately favorable family support, compared to 36.84% in whom family support was unfavorable. Thus, 47.4 % of the patients were moderately compliant with the treatment, while 29 % showed low adherence to it. Conclusion: the family support received by patients affected by tuberculosis, treated at the Manuel Ángel Higa Arakaki Hospital in Satipo, is significantly related to their degree of adherence to treatment.